EVALUATION OF MIXED AND COMPLEX FERTILIZERS FOR WETLAND RICE (Biological Sciences - PJSIR, 2022)
Three grades of mixed/complex fertilizers were field tested in wetland rice culture at Bangladesh Rice ResearchInstitute (BRRI) farm during dry and wet seasons of the year 1992using randomized complete block design with a viewto evaluate their effectiveness against straight fertilizers. Test varieties were BR3 and BRII for dry and wet seasons,respectively. Results implied that mixed/complex fertilizers were equally effective as straight fertilizers in increasinggrain yield of rice. Mineral nutrition of and nutrient removal by rice plants were also almost similar irrespective offertilizer sources.